PENGEMBANGAN BIG BOOK UNTUK MENINGKATKAN PENGETAHUAN CINTA LINGKUNGAN PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS II SEKOLAH - Azzahra, Patimah; Titin Sunaryati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to enhance environmental awareness using the Big Book as a medium in Pancasila education. The research was conducted at SDN Jayamukti 04, Cikarang Pusat, during the 2023/2024 academic year. This study follows a research and development (R&D) approach using the ADDIE model, with the research subjects being 29 second-grade students. The results of the study show that the Big Book media can improve environmental awareness among second-grade students, as evidenced by an increase in the average score on questionnaires administered during the learning process. The Big Book was deemed highly suitable for use, as demonstrated by expert evaluations in media, language, and content, which resulted in a score of 89.8%. The Big Book is considered effective in enhancing students' environmental awareness. This is supported by the pretest and posttest results, which show an N-Gain score of 0.8, falling into the high category. Therefore, the Big Book is declared effective for use as teaching material in schools.